(untitled) (Educational Dimension, 2023)
The organization of high school students’ research and learning activities in chemistry requires a significant amount of experimental work. The performance of experimental work in chemistry at school faces a number of problems, both purely material and organizational, to which the need for distance learning has recently been added. This article describes the state of use of augmented reality technologies in modern chemistry education and the possibilities of using augmented reality technologies to support students’ learning and research activities in chemistry. To solve the research tasks, cloud-based augmented reality development tools (A-Frame and AR.js) were used. The developed tool is a virtual chemistry laboratory using augmented reality technologies: individual markers correspond to reagents, and a pairwise combination of markers triggers a video recording of chemical interaction between the corresponding pair of reagents. The article describes the development of augmented reality software to support eleventh graders’ learning and research activities in chemistry in the form of an augmented reality-based virtual chemistry laboratory and its implementation in the teaching process.